PULMONARY FUNCTION TESTING IN YOUNG SCHOOL-age CHILDREN – СHALLENGES AND POSSIBILITIES - Stoilka Mandadzhieva; Blagoi Marinov; Stefan Kostianev (Science & Research)

(untitled)
Introduction: Pulmonary function testing is an essential clinical measurement in the assessment of children with respiratory diseases Purpose: The aim of this study was to evaluate the main difficulties in the assessment of lung function parameters in young schoolchildren. Materials and Methods: One hundred and seventy-nine healthy Bulgarian school children (90 males) in the age span 7 – 10 years took part in the study. All participants underwent anthropometric measurements – standing height, weight and body mass index (BMI). Studied group completed comprehensive pulmonary function assessment – slow and forced spirometry (MasterScreen Diffusion, Jaeger, Wuerzburg, Germany) in a certified laboratory applying the ATS and ERS criteria to ensure quality. Results: Spirometry performance standards and quality control in school-age children are the same as for adults. All participants were divided into age groups and our findings were that youngest children – aged 7 years - needed longer time for training and more efforts to produce technically acceptable spirometry results. Applying the start of test criteria: back-extrapolated volume ≤ 5% and within test criteria – flow-volume loop free from artifacts - were met by all studied children. Applying the end of test criteria - duration of forced expiration ≥ 6 sec. - we found that this criteria was not met by the studied group; 97 % had forced expiratory time (FET) less than 3 sec. Conclusions: Young schoolage children can perform spirometric measurements to meet currently established criteria after careful preparation and enough efforts. The recommendation for a minimum of 6 sec. FET should be modified especially in youngest children. The success rate of acceptable and repeatable spirometric tests increases with age.